#Quarantineworkout: The use of digital tools and online training among boxers and boxing coaches during the COVID-19 pandemic - Tjønndal, A. (Frontiers in Sports and Active Living, 2020)
The purpose of this article is to explore the use of online training strategies and digital tools amongst coaches and athletes in boxing clubs during the COVID-19 pandemic and the subsequent shutdown of organized sport. A digital qualitative research strategy was applied to boxing clubs, boxers, and boxing coaches in Norway. A total of 46 official clubs, athletes, and coach pages on Facebook were followed from 12th March-30th June 2020, resulting in a sample of 78 social media posts (texts, photos, and videos). A content analysis approach was used for the material. The results show that the use of digital tools amongst the studied Norwegian coaches and boxing clubs varied in frequency and form during the spring of 2020 (COVID-19 shutdown). For them, the most frequent use of digital instruments was to communicate internally and externally about the COVID-19 situation, national rules and guidelines. The material demonstrated that online training strategies varied between different constellations of three specific factors: (1) synchronized (live-streamed) online training and unsynchronized online training (at home training videos and programmes), (2) publicly published online training that was only accessible through digital registration, and (3) free online training and online training that was only available to paying members. For the athletes in the material, the most frequent content was social media posts for self-promotion purposes. Additionally, several of the athletes expressed that they struggled to cope with and manage the training at home during lockdown, and that they deeply missed training and competing as usual.